Pengaruh Working Capital Turnover dan Leverage Terhadap Financial Distress (Study Empiris pada Perusahaan Jasa SubSektor Property, Real Estate dan Kontruksi Bangunan yang Tercatat di Bursa Efek Indonesia) - Rahayu Lestari; Meta Ardiana (JFAS : Journal of Finance and Accounting Studies, 2020)
This study aims to determine whether or not the influence of Working Capital Turnover and Leverage to Financial Distress (Empirical Study on Service Company Sub Sector Property, Real Estate and Building Construction Listed on Indonesia Stock Exchange) during the period 2012-2017. Independent variable Working Capital Turnover using Net Working Capital Turnover and leverage using debt to assets ratio (DAR). The dependent variable of financial distress uses Z-Score Altman Modification. The research method used is quantitative method. The type of data is secondary data obtained from the official website of BEI namely www.idx.co.id. Data analysis used is multiple linear regression analysis. The results showed that the Working Capital Turnover variable had a positive effect on financial distress, meaning that if the faster or higher the working capital turnover, the financial condition would be fine and vice versa. Leverage variables have a negative effect on financial means that if the level of debt that finances assets is not too high, then the financial condition will be fine and vice versa.